2018
DOI: 10.3390/su10072415
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Product Design in Creating Circular Business Models: A Case Study on the Lease and Refurbishment of Baby Strollers

Abstract: In the transition to a circular economy companies are exploring new business models, implying a shift from selling products to offering products in circular business models, such as leasing. Product design is thought to play a crucial role in enabling this. Having a robust overview of relevant design roles and competencies is of foundational importance for the development of circular design tools and methods, and for the development of circular economy-based design curricula in higher education. However, how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 15 publications
1
41
0
4
Order By: Relevance
“…Circular Business Models and Circular User Engagement can be categorized as strategic competencies as these both aim at interventions at the business strategy level. The strategic competency "Circular Business Models" was identified in previous work before based on a single case study [28]. There was suggested that designers need to get more proficient in business model development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Circular Business Models and Circular User Engagement can be categorized as strategic competencies as these both aim at interventions at the business strategy level. The strategic competency "Circular Business Models" was identified in previous work before based on a single case study [28]. There was suggested that designers need to get more proficient in business model development.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of design for a circular economy, literature mentions the ability to design for multiple use cycles [28,29]. We consider this an anticipatory competency as it requires designers to develop a design that is "futureproof" and can be used during multiple cycles.…”
Section: Anticipatory Competencymentioning
confidence: 99%
See 3 more Smart Citations